Experimental Study of Liquid Jet Atomization and Penetration in Subsonic Crossflows - Minmin Wu; Shiqun Dai; Rui Ye; Mingxiong Ou; Guanqun Wang; Chao Hu; Xurui Fan; Weidong Jia (Agriculture)
This study experimentally investigates the breakup mechanisms and atomization characteristics of liquid jets in subsonic crossflows and develops a penetration depth model that incorporates the incidence angle. Experimental data show that the model fits well, with a minimum R2 value of 0.924 and an average of 0.969. High-speed imaging techniques were used to systematically analyze the effects of liquid- and gas-phase Weber numbers and incidence angles on the penetration and atomization of liquid jets. The experimental results indicate the following: (1) As the liquid Weber number (Wel) increases, the penetration depth increases, while the gas Weber number (Wea) is inversely related to penetration depth. (2) A decrease in the incidence angle (ranging from 45° to 90°) significantly reduces penetration performance. (3) As Wea increases, the volume median diameter (VMD) of droplets decreases by 61.70% to 83.09%, while smaller incidence angles cause a 42.96% increase in the VMD. The VMD shows a non-linear trend with respect to Wel, reflecting the complex interaction between inertial forces and surface tension. These findings provide a theoretical basis for understanding the atomization behavior of transverse jets and the key parameters affecting penetration and droplet formation. The results are of practical significance for the structural optimization and performance enhancement of air-assisted atomizing nozzles used in precision agricultural spraying systems.